Manajemen Pendidikan Anak Usia Dini (PAUD) dalam Rangka Meningkatkan Mutu Pembelajaran (Studi pada PAUD Negeri Pembina Curup dan PAUD Pertiwi Kabupaten Rejang Lebong) - Suharti, Suharti (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This article aims to find comparison of PAUD management of Pembina Curup and PAUD Pertiwi Rejang lebonmg in improving the quality of learning with qualitative descriptive approach so as to obtain the following conclusion. Curriculum management, student affairs, educators and educational staff, facilities and infrastructure and PAUD financial management has been implemented by the PAUD Pembina and PAUD Pertiwi. This is seen in, First, the quality of early childhood education is the service provided in the form of Kindergarten (TK) and Play Group (KB). Second, the fulfillment of the level of child development achievement, the learning is done in accordance with the age group of learners, and also in accordance with the needs of the surrounding community and the learners themselves. Third, the fulfillment of educators and educational personnel to meet the standards, even exceed the existing standards, by providing opportunities for educators to go to college and follow the training. Fourth, existing facilities and infrastructure are now more and more, both in terms of quantity and quality as required by the existing rules. Facilities and infrastructure about safe, comfortable, bright and fulfilling children's health criteria, according to the child's developmental level, make use of the available resources and potentials already fulfilled. Fifth, in accordance with the instructions and rules on the financial implementation of PAUD. Finance management of PAUD Terpadu and PAUD Pertiwi has also been communicated with parents, learners, and the community. So there is no rejection from the public.